Recent Advances in Lentiviral Vaccines for HIV-1 Infection - Norton, Thomas D.; Miller, Elizabeth A. (Frontiers in Immunology, 2016)
The development of an effective HIV vaccine to prevent and/or cure HIV remains a global health priority. Given their central role in the initiation of adaptive immune responses, dendritic cell (DC)-based vaccines are being increasingly explored as immunotherapeutic strategies to enhance HIV-specific T cells in infected individuals and, thus, promote immune responses that may help facilitate a functional cure. HIV-1-based lentiviral (LV) vectors have inherent advantages as DC vaccine vectors due to their ability to transduce non-dividing cells and integrate into the target cell genomic DNA, allowing for expression of encoded antigens over the lifespan of the cell. Moreover, LV vectors may express additional immunostimulatory and immunoregulatory proteins that enhance DC function and direct antigen-specific T cells responses. Recent basic and clinical research efforts have broadened our understanding of LV vectors as DC-based vaccines. In this review, we provide an overview of the pre-clinical and clinical LV vector vaccine studies for treating HIV to date. We also discuss advances in LV vector designs that have enhanced DC transduction efficiency, target cell specificity, and immunogenicity, and address potential safety concerns regarding LV vector-based vaccines.